Assuring the acquisition of expertise : apprenticeship in the modern economy - Zhao, Zhiqun [Herausgeber]; Rauner, Felix [Herausgeber]; Hauschildt, Ursel [Herausgeber] (Foreign Language Teaching and Research Press, 2011)
"Apprenticeship as model of work and training has numerous benefits for many different types of economies and societies and is nowadays been re-discovered in many countries all over the world. In May 2011, the International Network on Innovative Apprenticeship (INAP) hosted its fourth international conference in Beijing, China, bringing together leading researchers from 18 nations. The title of the conference 'Assuring the Acquisition of Expertise: Apprenticeship in the Modern Economy' indicates the need for apprenticeship to deliver on its promise of workplace skills and for it to develop and change as world economies develop. The international exchange of ideas among INAP members has been helpful to identify good practice and to facilitate the transfer of knowledge and innovation. This book is a summary of papers presented and discussed at the Beijing Conference paying special attention to the following four key topics: Developing curricula and qualification systems; Learning and development theories and models; Multiple roles of universities, schools and their teaching and training staff; Measuring competence development." (Verlag, BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; Berufsbildungssystem; Internationalisierung